Penguatan Branding UMKM Puspazary Melalui Inovasi Kemasan Dan Pemasaran Digital - Maharani Virginoni Zafitri; Diana Juni Mulyati (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Improving the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) is a primary focus in this digital era. This research explores efforts to enhance the branding of Puspazary MSMEs through packaging innovation and digital marketing strategies. The collaborative approach involves updating packaging design through re-branding photoshoots and digital marketing via Instagram. Through a two-month internship, the team focused on introducing the MSME, accessory production, marketing strategy analysis, content creation, and participation in innovation development. During the internship, re-branding photoshoots were implemented, packaging innovation by transitioning from cardboard to transparent ziplock, and digital marketing through Instagram. The results of these activities created a more attractive branding and increased competitiveness for Puspazary MSMEs, emphasizing the importance of innovative branding strategies in supporting MSME sustainability amid global market dynamics. The conclusion highlights the positive outcomes of implementing packaging and digital marketing innovations, while recommendations involve the continued development of digital-based branding strategies to expand market reach and enhance the resilience of Puspazary MSMEs in this digital era.